Factors Affecting the Learning Achievement of EFL Learners’ Speaking Skill at the University of Sulaimani - Hassan, Assistant Prof. Dr. Zana Mahmood; Ali, Shadan Ako (Sulaimani Journal for Humanities, 2023)
In the process of EFL learning, speaking is considered one of the most important skills. Language learners sometimes evaluate their success in EFL learning based on their fluency in the speaking skill. However, it is also believed to be a difficult skill to master because there are different factors which influence the EFL learners’ speaking abilities. This paper aims at investigating the correlation between affective factors and the learning achievement of EFL learners’ speaking skills and to find which factors have a positive effect and which ones have a negative one. The research is conducted using a quantitative method with the descriptive approach. A questionnaire and document analyses are utilized as the instrument to collect data. The participants of the study are 100 students from the English Department at the University of Sulaimani. The affective factors score and learning achievement score of the students are analyzed using a statistical analysis program called JMP-Pro 16. After analyzing the data, some conclusions are drawn based on the results and discussions, and the references are documented.
Keywords: Affective Factors; EFL Learning; Speaking Skills